FINANCIAL REPORTING: HIGHLIGHTING RESULTS AND STABILITY INDICATORS (European Journal of Economics, Finance and Business Development, 2024)
In the contemporary financial landscape, accurate and comprehensive reporting is crucial for stakeholders to assess an organization's performance and long-term viability. This article explores the integration of financial results and stability indicators within financial reports, emphasizing the importance of a balanced presentation that encompasses both immediate performance metrics and indicators of financial stability. By examining best practices in financial reporting, the article underscores the necessity for transparency and consistency in disclosing financial outcomes and stability measures. The discussion includes an analysis of key stability indicators such as liquidity ratios, solvency ratios, and operational efficiency metrics, illustrating how these can be effectively communicated alongside traditional financial results. The article aims to provide financial professionals with insights and strategies for enhancing the informativeness and reliability of financial reports, thereby supporting informed decision-making and fostering stakeholder confidence.